2016
DOI: 10.1007/s00198-016-3596-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential cost-effectiveness for using patient decision aids to guide osteoporosis treatment

Abstract: Patient decision aids have the potential to be cost-effective in osteoporosis so long as they increase adherence under certain conditions. Funding further research on the long-term effectiveness and costs of a patient decision aid which outlines all treatment options for osteoporosis patients is justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
8
1
2
Order By: Relevance
“…Several decision aids are already available in osteoporosis to support the decision to start an oral bisphosphonate or not, or to select an appropriate medication (2426). The use of decision aids has the potential to be cost-effective (27) and our results suggest that tailoring treatments to individual patients can increase their satisfaction with the treatment. As such, our findings might assist decision makers to identify treatments that are more likely to be cost-effective in practice (9).…”
Section: Discussionmentioning
confidence: 85%
“…Several decision aids are already available in osteoporosis to support the decision to start an oral bisphosphonate or not, or to select an appropriate medication (2426). The use of decision aids has the potential to be cost-effective (27) and our results suggest that tailoring treatments to individual patients can increase their satisfaction with the treatment. As such, our findings might assist decision makers to identify treatments that are more likely to be cost-effective in practice (9).…”
Section: Discussionmentioning
confidence: 85%
“…13 The proportions of patients initiating a specific DMD treatment or opting for best supportive care were therefore assumed to differ between the groups, also following studies for other health decisions. 24,25,42,43 The treatment initiation and treatment sequencing (i.e., the categorization of DMDs in first-line treatments for mild to moderate RRMS and in secondline treatments for highly active RRMS or RRMS not responding to first-line treatment) was informed by current clinical practice in the Netherlands, based on expert opinions and recommendations provided by the Dutch Healthcare Institute, 11 in the absence of formal up-todate clinical guidelines. Effects 2 and 3 were based on the theory by Stalmeier 26 that patients develop a more pronounced attitude toward taking the medication continuously and accurately.…”
Section: Intervention Effectsmentioning
confidence: 99%
“…Including the patient's preferences in treatment decisions may change the choice. 24,25,42,43 No evidence is yet available about how shared decision making could influence the treatment choice for MS. Based on stated preference studies, we constructed a possible profile regarding the initial treatment choice for the patients making a shared decision with their health care professional. Stated preference studies report that patients value the effects of the DMD most, more than safety, ease of use, and side effects.…”
Section: Intervention Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trenaman et al [ 10 ] found that a decision aid for patients considering total joint replacement was dominant, since it was cost saving and produced a small (not statistically significant) QALY gain. Penton et al [ 11 ] developed a hypothetical model of the cost effectiveness of a patient decision aid detailing the benefits and risks of bisphosphonates for patients with osteoporosis, finding the decision aid may have an incremental cost-effectiveness ratio below US$50,000/QALY.…”
Section: Introductionmentioning
confidence: 99%